PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO PIKTOGRAM (DIGA) PADA MATERI PIKTOGRAM UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN SUKORAME 2 KOTA KEDIRI - Febriana, Diah Dwi; Nurfahrudianto, Aan; Sahari, Sutrisno (STKIP Persada Khatulistiwa Sintang, 2024)
The aim of this developmental research is to determine the validity, student responses, and improvement in learning outcomes through the use of animated video learning media on pictogram material among fourth-grade students at SDN Sukorame 2 Kota Kediri. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of this study indicate that (1) the validation stage received an accumulated score of 87%, categorized as very good; (2) student responses received an accumulated score of 96%, also categorized as very good; and (3) the improvement on student learning outcomes using the animated video learning media was 55%. Therefore, the development of the animated video learning media on pictogram material is considered valid, practical, and effective.